Skiing Injuries - McIntyre, J. M. (1963)
This report, based on a study of 471 consecutive skiing accidents, is concerned with the contributory causes, mechanisms, treatment and prevention of the more common skiing injuries. Over 80% of injuries occur in skiers under the age of 30 years. Most injuries involve the lower extremities, and are ligamentous. One-third of all injuries are fractures. This distribution is the common experience in most ski centres which have organized facilities for treatment of such injuries. This study shows that rapid handling and early treatment of casualties ensures minimal suffering, accurate diagnosis, prevention of complications and earlier rehabilitation of injured skiers. Many of the causes of skiing accidents can be prevented by control of skiing conditions, and proper instruction of younger skiers.